PENGARUH PENERIMAAN DIRI TERHADAP PENYESUAIAN DIRI PENDERITA LUPUS - Paramita, Ratri; Margaretha, Margaretha (Jurnal Psikologi, 2013)
The study was conducted in 55 female adolescents (age 16-22 years) to determine whether there is effect of the self acceptance on the self adjustment of people living with Lupus. Data collection was conducted via self-report questionnaire of self acceptance consisting of 39 items and self adjustment questionnaire consists of 45 items; both scales were developed based on Mental Health theory by Schneiders (1964). Data analysis was performed with the statistical techniques of correlation and regression using SPSS version 16.0 for Windows. The result shows that there is a positive correlation between self-acceptance with self adjustment among people living with Lupus (r = 0.760, p < 0.001). Further regression analysis found the effect of self-acceptance to self adjustment among people living with Lupus (Î² = .863, r2 = .577). This research provides empirical evidence of the causal relationship between self-acceptance and self-adjustment among people living with Lupus.